ChemInform Abstract: Diastereoselective Passerini Reaction of Biobased Chiral Aldehydes: Divergent Synthesis of Various Polyfunctionalized Heterocycles. Issue 32 (22nd July 2016) - Moni, Lisa; Banfi, Luca; Basso, Andrea; Martino, Elisa; Riva, Renata
Abstract: Noteworthy, the carboxylic component of the Passerini reaction is the acetic acid in situ formed as the side product by the reduction of diacetoxyiodobenzene.